2017
DOI: 10.21474/ijar01/3783
|View full text |Cite
|
Sign up to set email alerts
|

Review on Recent Advances in Titanium Dye Oxide Nanoparticles for Dye Sensitized Solar Cell Applications.

Abstract: Alternate energy source becomes a crucial for green energy solution against ever increasing demand. Dye Sensitized solar cell is another promising option toward green energy providing opportunity to explore natural dye extracts from plants. This review explores recent developments in the field of Dye Sensitized solar cell technology specifically with sensitizer synthesized from plants which are also found in India. Anthocyanin, betalain, chlorophyll and carotenoids are among the most common plant pigments expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Iodide regenerates the sensitiser and the sensitiser is regenerated itself by the reduction of triiodide at the counter electrode. In this way, the circuit is completed by transferring electrons via the external load, as shown in Figure 3f in agreement with Divya et al [22].…”
Section: Basic Characterization Of the Fabricated Dsscsupporting
confidence: 88%
See 2 more Smart Citations
“…Iodide regenerates the sensitiser and the sensitiser is regenerated itself by the reduction of triiodide at the counter electrode. In this way, the circuit is completed by transferring electrons via the external load, as shown in Figure 3f in agreement with Divya et al [22].…”
Section: Basic Characterization Of the Fabricated Dsscsupporting
confidence: 88%
“…Sengupta et al [21] reported a conversion efficiency of 0.148% using dye from spinach leaves as the sensitiser. Divya et al [22] reviewed various attempts to fabricate solar cells using TiO 2 nanoparticles. Vallejo et al [23] synthesised and characterised composites of graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation